2022
DOI: 10.3346/jkms.2022.37.e35
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe COVID-19 in Children: A Systematic Review and Meta-Analysis

Abstract: Background Coronavirus disease 2019 (COVID-19) has been the most important global issue since December 2019. Although the clinical course of COVID-19 is known to be milder in children than in adults, associated hospitalizations among children have increased since the emergence of contagious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants and the achievement of a high vaccination rate in adults. Considering these global and domestic situations, we believe that risk stratificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
108
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 49 publications
3
108
0
7
Order By: Relevance
“…In the study presented, the majority of infected children were males (M/F: 3.2/1.0), but half of the girls developed a severe outcome. In our relatively small group, the male gender was not a risk factor for severe COVID-19 disease, as also stated in other papers [4,25].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the study presented, the majority of infected children were males (M/F: 3.2/1.0), but half of the girls developed a severe outcome. In our relatively small group, the male gender was not a risk factor for severe COVID-19 disease, as also stated in other papers [4,25].…”
Section: Discussionsupporting
confidence: 88%
“…The effect of prematurity was evaluated among children younger than 2 years of age in several studies [24,25]. They concluded that the risk of severe infection was two-fold higher in premature infants than in full-term infants (RR, 2.00; 95% CI, 1.63-2.46) [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown higher risks of severe Covid-19 and admission to an intensive care unit among children with coexisting conditions, 26 , 27 but we could not assess this because data were not available in the national Covid-19 vaccination registry. Nonetheless, the prevalence of coexisting conditions predisposing children to severe Covid-19 is probably low in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies show that other air pollutants, i.e., nitrogen oxides and ozone, may also affect the COVID-19 severity and mortality ( Mele et al, 2021 , Khorsandi et al, 2021 , Achebak et al, 2021 ). One should also note that the present investigation did not include the potential differences in socioeconomic factors, health behaviors (e.g., physical activity) and presence of comorbidities (e.g., chronic lung disease, diabetes, heart disease, immune deficiencies, seizure disorders, obesity,) that may affect the susceptibility of children to COVID-19 ( Choi et al, 2022 , Størdal et al, 2022 ). Moreover, the patient data were collected over 17 months, during which various SARS-CoV-2 variants emerged and dominated ( Hryhorowicz et al, 2021 , Jabłońska et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%